Ischemic Infarction of Pituitary Apoplexy: A Retrospective Study of 46 Cases From a Single Tertiary Center - Zhu, Qiang; Liang, Yuchao; Fan, Ziwen; Liu, Yukun; Zhou, Chunyao; Zhang, Hong; Li, Tianshi; Zhou, Yanpeng; Yang, Jianing; Wang, Yinyan; Wang, Lei (Frontiers in Neuroscience, 2022)
Object: Ischemic infarction of pituitary apoplexy (PA) is a rare type of pituitary apoplexy. In this study, we aimed to characterize ischemic PA at clinical presentations, imaging data, histopathological manifestations, and focus on the management and prognosis of it. Method: This study retrospectively identified 46 patients of ischemic PA confirmed by histopathology at a single institution from Jan 2013 to Dec 2020. The clinical presentations, imaging data, laboratory examination, management, and outcomes were collected in detail. We summarized clinical presentations, imaging characteristics, intraoperative findings, histopathological manifestations, and compared the outcomes based on the timing of surgical intervention. Result: Headache was the most common initial symptom (95.65%, 44/46), followed by visual disturbance (89.13%, 41/46), nausea, and vomiting (58.70%, 27/46). 91.3% of patients had at least one pituitary dysfunction. Hypogonadism was the most common endocrine dysfunction (84.78%, 39/46). Cortisol dysfunction occurred in 24 patients and thyroid dysfunction occurred in 17 patients. Typical rim enhancement and thickening of sphenoid sinus on MRI were seen in 85.37% (35/41) and 56.52% (26/46) respectively. Twelve and 33 patients underwent early (≤1 week) and delayed (>1week) transsphenoidal surgery (TSS) respectively. Total tumor resection was achieved in 27 patients, subtotal tumor resection in 19 patients. At surgery, cottage cheese-like necrosis was observed in 50% (23/46) of patients. At the last follow-up for 5.5 ± 2.7 years, nearly all patients obtained a significant improvement of visual disturbance regardless of surgical timing. 65% of the patients were still receiving long-term hormone replacement therapy. Conclusion: Patients with ischemic PA can be correctly diagnosed by typical imaging characteristics preoperatively. The timing of surgical intervention does not significantly affect the resolution of neurological and endocrinological dysfunctions. Preoperative endocrine dysfunctions are common and mostly appear to be poor after surgical intervention.